Phytase Supplementation under Commercially Intensive Rearing Conditions: Impacts on Nile Tilapia Growth Performance and Nutrient Digestibility - Rodrigues, Edgar Junio Damasceno [UNESP]; Ito, Paulo Incane [UNESP]; Ribeiro, Lucas Franco Miranda [UNESP]; de Carvalho, Pedro Luiz Pucci Figueiredo [UNESP]; Xavier, William dos Santos [UNESP]; Guimarães, Matheus Gardim [UNESP]; Junior, Ademir Calvo Fernandes [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP] (MDPI, 2023)
This study evaluated the effects of phytase supplementation on growth performance and apparent digestibility of Nile tilapia (Oreochromis niloticus) in a commercial fish farm setting. Nile tilapia (6300 male, 57.48 ± 1.04 g) were randomly stocked into 42 floating cages. The experimental design was completely randomized, comprising six treatments and seven replications. Fish were fed five phosphorus deficient plant-based diets with graded levels of phytase supplementation (0, 500, 1000, 1500, 2000 UF kg−1) and an additional diet containing phosphorus supplementation to meet the requirement of this fish species (positive control). After 97 days of feeding, growth performance data were collected and 900 fish (500 ± 10 g) were relocated to 6 floating cages for the digestibility assessment. Quadratic polynomial regression analysis indicated 1537.5 and 1593.2 UF kg−1 as the optimum dietary levels for daily weight gain and feed conversion rate, respectively. Including 2000 UF kg−1 resulted in the higher dry matter, crude protein, energy, and ash apparent digestibility coefficient values. Therefore, phytase supplementation from 1500 to 2000 UF kg−1 is recommended to enhance growth performance and nutrient bioavailability of Nile tilapia reared according to industry practices.
Keywords: digestibility; feed additive; fish farming; floating cages; Oreochromis niloticus